Risk Factor of Neovascular Agerelated Macular Degeneration Progression after Cataract Surgery - V. G. Likhvantseva; S. G. Kapkova; S. I. Rychkova; V. I. Naumova (Oftalʹmologiâ)
The prevalence of late AMD, including neovascular AMD or geographic atrophy, and cataract in the same eye after age 80 years is estimated to be 12 and 68 %, respectively. There is currently no consensus on whether cataract surgery is beneficial or harmful for people with dry AMD. Although cataract surgery has been reported to provide better visual outcomes in eyes with AMD 6 months after surgery compared with previously followed eyes, it is unclear whether the timing of surgery relative to the start of AMD treatment influences long-term outcomes. The question of risk factors predisposing to the occurrence of exudation after cataract surgery in people with nAMD remains controversial.